ANALISIS KEJADIAN DEMAM BERDARAH DENGUE DENGAN PENDEKATAN SISTEM INFORMASI GEOGRAFIS DI KABUPATEN BULELENG - Kurniasari, Ni Made Dian; Putri, Putu Tiya Pradnyani S (ARCHIVE OF COMMUNITY HEALTH, 2024)
In 2020, DHF cases in Bali Province will increase significantly with an incidence rate of 278.6 per 100,000 population. Most DHF cases occur in Buleleng Regency with an incidence rate of 512 per 100,000 during 2021. The purpose of this study is to provide regional information regarding the distribution of DHF incidents in Buleleng Regency. This research is a type of descriptive research with an ecological study design. This research was conducted in Buleleng Regency with a sample of all DHF sufferers in 2021. Data were analyzed descriptively and mapped using QGIS 3.16 to produce a choropleth map. The results showed that out of 990 cases, the number of DHF sufferers in men had an incidence rate of 135.88 per 100,000 population of the male sex with the most cases being found at the age of 17-25 years with an incidence rate of 280.26 per 100,000 population with an age range 17 – 25 years. Buleleng sub-district had the most cases among other sub-districts, namely 361 (36.64%). Population density is related to the incidence of DHF. DHF cases were also found clustered 500 meters around the TPS. High cases also tend to be found in areas with low larvae free numbers. Strengthening DHF surveillance and keeping the environment clean are activities that must be carried out routinely by the government and supported by the community. Keywords: Dengue Hemorrhagic Fever, Geographic Information System, Territoriality